2011
DOI: 10.5005/jp-journals-10071-23367
|View full text |Cite
|
Sign up to set email alerts
|

Global Trigger Tool: Proficient Adverse Drug Reaction Autodetection Method in Critical Care Patient Units

Abstract: Background: Emergency department (ED) being the most crucial part of hospital, where adverse drug reactions (ADRs) often go undetected. Trigger tools are proficient ADR detection methods, which have only been applied for retrospective surveillance. We did a prospective analysis to further refine the trigger tool application in healthcare settings. Objective: To estimate the prevalence of ADRs and prospectively evaluate the importance of using trigger tools for their detection. Materials and methods: A prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The use of sedation has a PPV of 0.67 this may be due to the administration of sedation used as a response to the occurrence of insomnia side effects after antimicrobial administration. Another study conducted by previous researchers also showed that the increase in BUN (Blood Urea Nitrogen), the use of antiemetics (Naessens, et al, 2010) and antihistamines (Pandya et al, 2020) were also sensitive enough to detect ADR.…”
Section: Kusumawardani Maria and Amartamentioning
confidence: 86%
“…The use of sedation has a PPV of 0.67 this may be due to the administration of sedation used as a response to the occurrence of insomnia side effects after antimicrobial administration. Another study conducted by previous researchers also showed that the increase in BUN (Blood Urea Nitrogen), the use of antiemetics (Naessens, et al, 2010) and antihistamines (Pandya et al, 2020) were also sensitive enough to detect ADR.…”
Section: Kusumawardani Maria and Amartamentioning
confidence: 86%
“…In the present study, we found a low performance of triggers such as "antiemetic administration" and "increased blood urea nitrogen or serum creatinine" to cause harm. Silva et al (2018) and Patel et al (2020) identified antiemetic administration as the most frequent trigger in human patients that are hospitalized. However, antiemetic administration presented the lowest performance compared with the other triggers due to the large number of false-positive cases, corroborated by our findings (Silva et al, 2018;Patel et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al (2018) and Patel et al (2020) identified antiemetic administration as the most frequent trigger in human patients that are hospitalized. However, antiemetic administration presented the lowest performance compared with the other triggers due to the large number of false-positive cases, corroborated by our findings (Silva et al, 2018;Patel et al, 2020). Furthermore, in another study conducted in humans, Brenner et al (2012) evaluated abnormal laboratory parameters as triggers for the detection of ADEs in outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Pandya and Patel et al [8] have taken the advantage of Electronic Health Records (EHR) where numerous clinical narratives and notes are written by physicians, nurses, and even by the patients themselves to generate new TTs. Using statistical correlation approaches, the authors have identified new TTs.…”
Section: Related Workmentioning
confidence: 99%
“…The literature on ADR extraction showed a high dependency on the trigger terms utilization within the ADR detection task [7,8]. The utilization of trigger terms represents different challenging issues.…”
Section: Introductionmentioning
confidence: 99%